Naphthalene-triazolopyrimidine hybrid compounds as potential multifunctional anti-Alzheimer's agents. Issue 14 (15th July 2019) - Umar, Tarana; Gusain, Siddharth; Raza, Md Kausar; Shalini, Shruti; Kumar, Jitendra; Tiwari, Manisha; Hoda, Nasimul
Graphical abstract: Abstract: In an attempt to construct potential anti-Alzheimer's agents Naphthalene-triazolopyrimidine hybrids were synthesized and screened in vitro against the two cholinesterases (ChE)s, amyloid β aggregation and for antioxidation activity. Single-crystal X-ray crystallography was utilized for crystal structure determination of one of the compounds. In vitro study of compounds revealed that most of the compounds are capable of inhibiting acetylcholinesterase and Butyrylcholinesterase activity. Particularly, the compounds 4e and 4d exhibited IC50 values ranging from 8.6 to 14 nM against AChE lower than the standard drug Donepezil (IC50 49 nM). Best result was found for compound 4e with IC50 of 8.6 nM (for AChE) and 150 nM (for BuChE). Selectivity upto that of Donepezil and even more was observed for 4a, 4c and 4h . Investigation by electron microscopy, transmission electron microscopy and ThT fluorescence assay unveils the fact that synthesized hybrids exhibit amyloid β self-aggregation inhibition. The compounds 4i and 4j revealed highest inhibitory potential, 85.46% and 72.77% at 50 μM respectively; above the standard Aβ disaggregating agent, Curcumin. Their antioxidation profile was also analyzed. Studies from DPPH free radical scavenging assay and ORAC assay depicts molecules to possess low antioxidation profile. Results suggest that triazolopyrimidines are potential candidate for Acetylcholinesterase (AChE), Butyrylcholinesterase (BuChE), and amyloid β aggregation inhibition. In silico ADMET profiling indicates drug-like properties with a very low toxic influence. Such synthesized compounds provide a strong vision for further development of potential anti-Alzheimer's agents.